NR4A nuclear receptors in T and B lymphocytes: Gatekeepers of immune tolerance. Issue 1 (17th February 2022) - Hiwa, Ryosuke; Brooks, Jeremy F.; Mueller, James L.; Nielsen, Hailyn V.; Zikherman, Julie
Abstract: Random VDJ recombination early in T and B cell development enables the adaptive immune system to recognize a vast array of evolving pathogens via antigen receptors. However, the potential of such randomly generated TCRs and BCRs to recognize and respond to self‐antigens requires layers of tolerance mechanisms to mitigate the risk of life‐threatening autoimmunity. Since they were originally cloned more than three decades ago, the NR4A family of nuclear hormone receptors have been implicated in many critical aspects of immune tolerance, including negative selection of thymocytes, peripheral T cell tolerance, regulatory T cells (Treg), and most recently in peripheral B cell tolerance. In this review, we discuss important insights from many laboratories as well as our own group into the function and mechanisms by which this small class of primary response genes promotes self‐tolerance and immune homeostasis to balance the need for host defense against the inherent risks posed by the adaptive immune system.